Analisis Alur Naskah Drama Nilam Binti Malin Karya Karta Kusumah - Sekar Wangi Arasti Yasmin; Wimbrayardi Wimbrayardi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This study aims to analyze the plot of the drama script "Nilam binti Malin" by Karta Kusumah which is seen from the overall development of the plot. This research uses a qualitative approach with descriptive analytical methods. This research instrument is the researcher himself as the main instrument, data collection is carried out through the stages of literature study, observation, interviews, and documentation. The steps in analyzing data are collecting data, describing the data, analyzing, and making conclusions. The results showed that the plot of the drama Nilam bint Malin used Henshaw's Montage theory, namely Exposition, Generating Circumstance, Rising Action, Climax, Falling Action, and Cata Strophe. The exposition introduces the character of Nilam, Malin's daughter, as well as other figures such as Malin, Mandeh, Warga, Kru Kapal, and Tukang Kaba. The flow of events began to move right when Patchouli arrived at Air manis Beach and began to know about problems in the village. Until the part where the situation began to heat up where Nilam began to know the problems that existed in Air Manis village and Nilam knew what was the reason behind her father who was petrified on the beach.